2006
DOI: 10.1148/radiol.2381040088
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia Pneumoniae: Comparison with Findings ofMycoplasmaPneumoniaeandStreptococcusPneumoniaeat Thin-Section CT

Abstract: C pneumoniae pneumonia demonstrates a wide spectrum of thin-section CT findings that are similar to those of S pneumoniae pneumonia and M pneumoniae pneumonia; airway dilatation and bronchovascular thickening were significantly more frequent in patients with C pneumoniae pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 15 publications
4
73
2
1
Order By: Relevance
“…S. pneumoniae, Klebsiella pneumoniae, Mycoplasma pneumoniae and Chlamydia pneumoniae are also common pathogens involved in community-acquired or nosocomial pneumonia. The average age of patients with M. catarrhalis infection tended to be greater than that of patients with pneumonia caused by other pathogens such as S. pneumoniae, K. pneumoniae, M. pneumoniae or C. pneumoniae (60 years, 61.5 years, 47.3 years and 57.7 years, respectively) [32][33][34]. Among the 109 patients with pulmonary infection caused by M. catarrhalis alone, pulmonary emphysema (67.9%) was the most commonly associated condition, followed by smokers (43.1%), cardiovascular disease (40.4%), malignant disease (37.6%), alcoholism (22.9%) and diabetes mellitus (16.5%).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…S. pneumoniae, Klebsiella pneumoniae, Mycoplasma pneumoniae and Chlamydia pneumoniae are also common pathogens involved in community-acquired or nosocomial pneumonia. The average age of patients with M. catarrhalis infection tended to be greater than that of patients with pneumonia caused by other pathogens such as S. pneumoniae, K. pneumoniae, M. pneumoniae or C. pneumoniae (60 years, 61.5 years, 47.3 years and 57.7 years, respectively) [32][33][34]. Among the 109 patients with pulmonary infection caused by M. catarrhalis alone, pulmonary emphysema (67.9%) was the most commonly associated condition, followed by smokers (43.1%), cardiovascular disease (40.4%), malignant disease (37.6%), alcoholism (22.9%) and diabetes mellitus (16.5%).…”
Section: Discussionmentioning
confidence: 88%
“…The abnormal findings were predominantly seen in the lower zone and in the peripheral lungs. Nambu et al [32] reported that the CT findings in 41 patients with S. pneumoniae pneumonia consisted mainly of consolidation, reticular opacity and centrilobular nodules (90%, 39% and 32%, respectively). Previously, we have reported chest CT findings in 198 patients with acute K. pneumoniae pneumonia alone [33], in 42 patients with M. pneumoniae pneumonia alone [34] and in 40 patients with C. pneumoniae pneumonia alone [34].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the presence of bilateral bronchial wall thickening or centrilobular nodules may be highly suggestive for M. pneumoniae pneumonia. Nambu et al reported that the difference in frequency of bronchovascular bundle thickening (bronchial wall thickening) and peribronchovascular or centrilobular nodules between M. pneumoniae and S. pneumoniae was statistically significant (p = 0.004) [15]. Air-space consolidation with or without centrilobular or peribronchovascular nodules were often seen in both pneumonias and were nonspecific.…”
Section: Discussionmentioning
confidence: 99%
“…However, using this system there are still many cases where the guidelines cannot differentiate between M. pneumoniae pneumonia and S. pneumoniae pneumonia, and the JRS guidelines are seeking new specific parameters in order to improve this scoring system [4]. Some reports have focused on radiographic features using high-resolution computed tomography (HRCT) of M. pneumoniae pneumonia [11][12][13][14][15]. However, to our knowledge, there have been relatively few comparative studies that have investigated the radiographic findings of M. pneumoniae pneumonia versus S. pneumoniae pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Children's infectious ILD are mostly attributed to primary airway infections. The infections of viruses, mycoplasma, and chlamydia first spread along the trachea and then pass through small and medium-sized bronchi, forming axial interstitial inflammation (Nambu et al, 2006). Airway mucosa and submucosa involvement caused by repeated infection is the main reason for the abnormal changes of bronchovascular bundles.…”
Section: Bronchovascular Bundle Abnormalitiesmentioning
confidence: 99%